Lipid nanoparticle–mediated in vivo generation of panCAR immune cells for solid tumor immunotherapy - Qimeng Yin; Xue Liang; Chenchen Zhang; Yuerong Bai; Jiahao Li; Feng Qian; Min Qiu (Proceedings of the National Academy of Sciences, 2026)
Adoptive cell therapies that genetically engineer immune cells with chimeric antigen receptors (CARs) have shown limited success against solid tumors due to the immunosuppressive tumor microenvironment (TME) and logistical challenges of ex vivo cell manipulation. Here, we introduce an immune cell-tropic lipid nanoparticle (LNP) platform that enables systemic delivery of CAR-encoding mRNA for the in vivo generation of panCAR immune cells. A single intravenous injection of this LNP system efficiently and transiently engineers T cells, macrophages, dendritic cells, and NK cells across the spleen, bone marrow, and peripheral blood, yielding a synergistic, multilineage antitumor response. Using human epidermal growth factor receptor 2 (HER2) as a CAR target, we demonstrate that repeated administration of LNP formulated with HER2-CAR mRNA (LNP-panCAR HER2 ) effectively inhibits tumor growth and prolongs overall survival in three murine syngeneic xenograft tumor models, without causing obvious side effects. Immune profiling of treated tumors reveals a remodeled TME with a shift toward an immunostimulatory phenotype, characterized by reduced M2-like macrophages and an increased presence of effector T cell subsets. Our findings establish LNP-panCAR as a broadly applicable, off-the-shelf in vivo CAR cell therapy platform for solid tumor immunotherapy and beyond.